Failing to pay heed to health warnings in a food-associated environment. (1st January 2018) - Verhoeven, Aukje A.C.; Watson, Poppy; de Wit, Sanne
Abstract: People often fail to adhere to food-related health information. Increasing evidence suggests that environmental stimuli interfere with good intentions by triggering choices relatively automatically. Using a Pavlovian-instrumental transfer (PIT) task, we examined whether food-associated stimuli reduce health warnings' effectiveness. We expected that people adhere to health warnings in the absence, but not presence, of food-associated stimuli. In addition, we examined timing effects, i.e., whether health warnings are more effective when they are given prior to associative learning rather than afterwards. In the PIT task, participants learned to press keys for two food rewards (instrumental learning) and associations between stimuli and these rewards (Pavlovian learning) in separated phases. Health warnings about one reward were given after associative learning (Study 1), or before versus afterwards (Study 2). During test phase, participants pressed for food outcomes while occasionally food-related stimuli were presented. In absence of food-related stimuli, participants increased responding for rewards perceived as more healthy. However, when stimuli were present, responding was biased towards the signaled outcome, regardless of health warnings or timing. Health messages influence food choice behavior, but are no longer effective when food-associated stimuli are present. This provides important insights why health warning effects might be limited in an obesogenic environment.